Organics in the stratosphere: new insights from weather balloon flights conducted in France - Roland Benoit; Hazel Vernier; Jean-Paul Vernier; Lilian Joly; Nicolas Dumelié; Gisèle Krysztofiak; Loïc Vieille; Sandrine Delpeux; Cyril Crevoisier; Philippe Dagaut; Gwenaël Berthet (npj Climate and Atmospheric Science)
Abstract Atmospheric aerosols significantly influence the Earth’s climate, yet they remain a major source of uncertainty in climate projections. Here, we present a set of unique offline analysis of organics collected from the ground to the stratosphere with ultimate sensitivity using a new balloon-borne sampling technique deployed on simple weather balloons. Activated and functionalized carbon fabrics were used to target chemical compounds in the gaseous and aerosol forms during three flights over France. Ultra-high-resolution mass spectrometry, enabling the detection of thousands of organic compounds, and highlighted high-carbon-number organics, indicating oligomerization in long-lived tropical stratospheric air masses. Our measurements suggest that large stratospheric sulfate aerosols from volcanic eruptions could play a role in the formation of secondary aerosols in internally mixed particles and may explain the presence of organics with higher carbon numbers. These measurements revealed a drop in the number of unsaturated carbons at higher altitudes.